The impact of the bank regulation and supervision on the efficiency of Islamic banks - Bakri, Mohammed Hariri; Mohd Noor, Nor Halida Haziaton; Wan Yusof, Wan Yusrol Rizal; Mohd Noor, Nor Raihana Asmar; Zainal, Nurazilah (Korea Distribution Science Association (KODISA), 2020)
This study investigates the impact of bank regulation and supervision on the efficiency of banking sectors on 108 Islamic banks from 26 countries offering Islamic banking and finance products and services. The technical efficiencies of individual Islamic banks have been analyzed using the data envelopment analysis method (DEA). The ordinary least square estimation method is employed to examine the impact of country supervision and regulation on the technical efficiency of Islamic banks. The empirical findings suggest that supervisory power, activity restrictions and private monitoring positively influence the efficiency of Islamic banks. The study revealed that Islamic banks that are operating in Middle East and North Africa (MENA) and middle-income countries are more technically efficient given the less stringent rules on capital requirement and we found that there is statistically significant evidence that higher capital requirements are negatively associated with the efficiency of Islamic banks. The empirical findings of this study are expected to help policy-makers and government officials to better understand how their decisions affect the performance.